Regulation of Phosphorylated State of NMDA Receptor by STEP61 Phosphatase after Mild-Traumatic Brain Injury: Role of Oxidative Stress - Carvajal, Francisco J.; Cerpa, Waldo (My University, 2021)
Traumatic Brain Injury (TBI) mediates neuronal death through several events involving many molecular pathways, including the glutamate-mediated excitotoxicity for excessive stimulation of N-methyl-D-aspartate receptors (NMDARs), producing activation of death signaling pathways. However, the contribution of NMDARs (distribution and signaling-associated to the distribution) remains incompletely understood. We propose a critical role of STEP61 (Striatal-Enriched protein tyrosine phosphatase) in TBI; this phosphatase regulates the dephosphorylated state of the GluN2B subunit through two pathways: by direct dephosphorylation of tyrosine-1472 and indirectly via dephosphorylation and inactivation of Fyn kinase. We previously demonstrated oxidative stress's contribution to NMDAR signaling and distribution using SOD2(+/-) mice such a model. We performed TBI protocol using a controlled frontal impact device using C57BL/6 mice and SOD2(+/-) animals. After TBI, we found alterations in cognitive performance, NMDAR-dependent synaptic function (decreased synaptic form of NMDARs and decreased synaptic current NMDAR-dependent), and increased STEP61 activity. These changes are reduced partially with the STEP61-inhibitor TC-2153 treatment in mice subjected to TBI protocol. This study contributes with evidence about the role of STEP61 in the neuropathological progression after TBI and also the alteration in their activity, such as an early biomarker of synaptic damage in traumatic lesions.
Keywords: mild traumatic brain injury; & nbsp